The skin prick test results to saffron, sumac and barberry in patients with atopy - Seyed Hesamedin Nabavizadeh; Mozhgan Moghtaderi; Soheila Aleyasin; Hossein Esmaeilzadeh; Mohammadmehdi Araghi (Global Journal of Allergy - Peertechz Publications, 2019)
Background: Food allergens appear to play a role in the etiology and deteriorating of atopy in some patients, little is known about hypersensitivity to some common food additives in these patients. The purpose of this study was to identify probable sensitization to saffron, sumac and barberry in patients with atopy. Materials and Methods: This cross- sectional study included 390 patients with atopy and 300 healthy individuals with no history of atopic diseases. Skin tests were performed in both patient and control group with saffron, sumac and barberry.